Leviathan as a Minority Shareholder: Firm-Level Implications of State Equity Purchases - Inoue, Carlos F. K. V.; Lazzarini, Sergio G.; Musacchio, Aldo (Academy of Management Journal, 2013)
In many countries, firms face institutional “voids” that raise the costs of doing business and thwart entrepreneurial activity. We examine a particular mechanism that may address those voids: minority state ownership. Minority stakes are less affected by the “agency distortions” commonly found for full-fledged state ownership. Using panel data from publicly traded firms in Brazil, where the government holds minority stakes through its development bank, we find a positive effect of those stakes on firms' returns on assets and on the capital expenditures of financially constrained firms with investment opportunities. However, these positive effects are substantially reduced when minority stakes are allocated to business group affiliates and as local institutions develop. Therefore, we shed light on the firm-level implications of minority state ownership, a topic that has received scant attention in the strategy literature.